Evaluation of exosomal miR-155, let-7g and let-7i levels as a potential noninvasive biomarker among refractory/relapsed patients, responsive patients and patients receiving R-CHOP. Issue 8 (3rd July 2019) - Zare, Nasrin; Haghjooy Javanmard, Shaghayegh; Mehrzad, Valiollah; Eskandari, Nahid; Kefayat, Amirhosein
Abstract: This study aimed to investigate and compare exosomal miR-155, let-7g and let-7i levels as a noninvasive biomarker among patients with refractory/relapsed or responsive DLBCL after R-CHOP treatment and patients receiving R-CHOP. Plasma was collected and exosomes were isolated from plasma. Exosomes confirmed by zeta-seizer, electron microscope, and western blot. Exosomes concentration was investigated by BCA assay. MiR-155, let-7g and let-7i levels were evaluated in plasma-derived exosomes by real-time PCR. Plasma IFN-γ and IL-4 level were measured by ELISA assay. We observed the significant increase in the exosomal miR-155 levels ( p  = .002) and exosomes concentration ( p  = .001) in refractory/relapsed patients compared to responsive patients and patients receiving R-CHOP. No association was not observed between exosomal miR-155 levels and IPI and disease stage. The significant decrease in IFN-γ levels was observed in patients receiving R-CHOP compared to refractory/relapsed or responsive patients ( p =.001). Therefore, exosomal miR-155 might be useful as potential prognostic biomarkers to predict response to treatment in DLBCL patients.